Social Tolerance of Baghdad College students and its Relation With Parental Treatment Styles (Journal Of Educational and Psychological Researches, 2011)
The social tolerance is one of the important variables in personality; it helps growth and development of individual's personality. Theories and the students affirmed that social Tolerance affects the society growth and development as well.The presents study aims:1. Estimating the social Tolerance for Baghdad College students.2. Realizing how College students vary in social Tolerance according to:Sex, (Male, Female) ٍSpecialization (Scientific, Humanity).3. Realizing the nature of relationship between social Tolerance of College students and father and mother styles. To achieve this research goals the researcher established parameter (scale) for social Tolerance applied to sample of (500) students male and female. The result indicated that the College students have poor social Tolerance and there is no significant differences between male and female and no differences between the student according to specializations well.In the light of the achieved result the researcher recommended and suggested many things which can raise the social Tolerance concept.